Split-Second Unlearning: Developing a Theory of Psychophysiological Dis-ease - Hudson, Matt; Johnson, Mark I. (Frontiers in Psychology, 2021)
Psychophysiological ‘stress’ underpins many conditions including anxiety, depression, phobias, chronic fatigue syndrome and non-specific musculoskeletal pain such as fibromyalgia. In this article we develop an understanding of chronic psychophysiological stress from a psychological educational perspective, by drawing on supporting evidence that significant emotional events in early life (traumatic and benign) can influence health and well-being later in life. We suggest that traumatic events instigate psychophysiological ‘stress’ responses and the formation of emotional memory images (EMIs) within very short time frames, i.e. ‘split-second learning’. Once formed these emotional memories are triggered in daily living ‘re-playing’ psychophysiological stress responses, resulting in chronic psychophysiological ‘dis-ease’. We describe a novel therapeutic approach to scan clients for mannerisms signifying a subconscious ‘freeze-like’ stress response that involves the client as a curious observer within their own experience, feeding back the non-verbal cues as they arrive in the moment. By breaking down the observable fragments of their split-second Pavlovian response to the trigger clients can detach their EMI from the psychophysiology stress response i.e. ‘split-second unlearning’. Our split-second unlearning model recognises the EMI as a barrier to moving forward and needs to be unlearned before the client can become naturally adaptive again. We argue that this approach enables places the client at the centre of the work without the need of getting bogged down in a life-long narrative.